Eyaculación precoz y funcionalidad en el subsistema conyugal - Campos Reyes, Martha Susana (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
PREMATURE EJACULATION -. 's Persistent or recurrent ejaculation with minimal sexual stimulation happens before the patient or his partner would want (n) associated with a personal or couple discomfort. Premature ejaculation may be associated with low self esteem and the presence of marital problems. . Marital dysfunction - is the change in the marital subsystem functions and cause imbalance such as: communication, allocation and assumption of roles, sexual satisfaction, affect and decision making. Conjugal functionality is an item that the family physician should consider for them comprehensively and easily in your daily practice. OBJECTIVE-. Relate premature ejaculation with functionality in the marital subsystem MATERIALS AND METHODS. 126 couples who have a spousal beneficiary of IMSS80.SePEDT I apply the questionnaire, used to assess premature ejaculation were included in the questionnaire were conducted on marital dysfunction Chavez Aguilar couples to compare if ejaculation is due marital dysfunction. At the same time appreciate if premature ejaculation is related to the following variables socio demographic such as age, education, marital status, occupation, religion, was determined by biochemical studies that have problems with glucose, cholesterol and triglycerides. RESULTS -. 126 couples studied the incidence of premature ejaculation 3.2% (4) were found. When comparing the differences between the groups with and without premature ejaculation based on their marital functioning observed a lower frequency of marital dysfunction in patients with premature ejaculation. CONCLUSIONS -. Study shows that premature ejaculation is not a cause of marital dysfunction.

La eyaculación precoz.- es la eyaculación persistente o, recurrente, con un mínimo de estimulación sexual, que sucede antes de que el paciente o su pareja lo desee(n), asociada con una incomodidad personal o de pareja. La eyaculación precoz Puede estar asociada con baja autoestima y la presencia de problemas conyugales. La disfunción conyugal.- es la alteración en las funciones del subsistema conyugal y que provocan desequilibrio como lo son: comunicación, adjudicación y asunción de roles, satisfacción sexual, afecto y toma de decisiones. La funcionalidad conyugal es un elemento que el médico familiar debe tener en cuenta para detectarla en forma integral y sencilla en su consulta diaria OBJETIVO.- relacionar la eyaculación precoz con la funcionalidad en el subsistema conyugal MATERIAL Y METODOS. Se incluyeron 126 parejas que tuvieran una relación conyugal derechohabiente del IMSS 80.Se le aplico el cuestionario PEDT, que sirve para valorar la eyaculación precoz, se les realizo el cuestionario de disfunción conyugal el de Chávez Aguilar a las parejas para comparar si la eyaculación si es causa de disfunción conyugal. Al mismo tiempo se valoro si la eyaculación precoz tiene relación con las siguientes variables socio demográficas como son la edad, y escolaridad, estado civil, ocupación, religión, se determino por medio de estudios bioquímicos que tuvieran problemas con la glucosa, colesterol y triglicéridos. RESULTADOS.- de los 126 parejas estudiadas se encontró una incidencia de eyaculación precoz 3.2%(4).Al comparar las diferencias entre los grupos con y sin eyaculación precoz con base a su funcionamiento conyugal observamos una menor frecuencia de disfunción conyugal en los pacientes con eyaculación precoz. CONCLUSIONES.- el estudio demuestra que la eyaculación precoz no es causa de disfunción conyugal.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4239; info:eu-repo/classification/cti/3; FCMB-E-2015-0520; Eyaculación precoz; Disfunción; Subsistema conyugal